2022
DOI: 10.1186/s12872-022-02547-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP2C19 genetic polymorphism on the pharmacodynamics and clinical outcomes for patients treated with ticagrelor: a systematic review with qualitative and quantitative meta-analysis

Abstract: Background Studies show inconsistent results regarding the impact of CYP2C19 genotype on the pharmacodynamics (PD) and clinical outcomes of ticagrelor. With the implementation of genotype-guided individualized antiplatelet therapy, the association between CYP2C19 polymorphism and the efficacy and safety of ticagrelor for patients is still worthy of exploring and studying. Methods This systematic review protocol has been registered in the PROSPERO n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 59 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Some studies have searched for possible associations between the effect of ticagrelor and the CYP2C19 polymorphism, but the data reported are controversial. The study by Xie et al suggested that the CYP2C19 polymorphism could be related to an increased risk of bleeding in Asian patients who received treatment with ticagrelor [43]. Teng reported that CYP2C19 appeared to have no impact on the pharmacodynamic characteristics of ticagrelor [10].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have searched for possible associations between the effect of ticagrelor and the CYP2C19 polymorphism, but the data reported are controversial. The study by Xie et al suggested that the CYP2C19 polymorphism could be related to an increased risk of bleeding in Asian patients who received treatment with ticagrelor [43]. Teng reported that CYP2C19 appeared to have no impact on the pharmacodynamic characteristics of ticagrelor [10].…”
Section: Discussionmentioning
confidence: 99%